Prevalence and associated factors of social skills deficits in patients with depressive disorders at Psychiatric Outpatient Department, King Chulalongkorn Memorial Hospital - Kurimoto, Pitima; Lueboonthavatchai, Peeraphon (Chulalongkorn Medical Journal, 2021)
Background: Social skills deficits are present in 43.3% of the depressed patients, significantly impact the quality of life and may result in severe and chronic depression. However, studies concerning social deficits in Thai depressed patients were still limited. Objective: To determine the prevalence and associated factors of social skills deficits of Thai patients with depressive disorders. The associated factors included severity of depression, satisfaction with family function, self-esteem, and personality characteristics. Methods: We recruited 150 patients aged 18 years and above diagnosed with major depressive disorder or persistent depressive disorder (dysthymia) using DSM-5 criteria. All subjects completed 5 questionnaires: 1) Beck Depression Inventory-II (BDI-II) - Thai version; 2) Social Skill Inventory (SSI) - Thai version; 3) Family Adaptation, Partnership, Growth, Affection, Resolve (APGAR) Questionnaire; 4) Revised Version of Thai Rosenberg Self-Esteem Scale (Revised Thai RSES); and, 5) Maudsley Personal Inventory (MPI). Logistic regression was performed to identify the potential predictors of social skills deficits. Results: The prevalence of social skills deficits in depressed patients was 46.7%. The mean score of social skills was 78.1 ± 16.5. Factors associated with social skills deficits were being female, age under 40 years (P < 0.05), moderate-to-severe level of depression, low-to-moderate satisfaction level of family function, low level of self-esteem, introvert personality, and neurotic personality (P < 0.01). By logistic regression analysis, the significant predictors of social skills deficits were introvert personality (P < 0.01) and the moderate-to-severe level of depression and neurotic personality (P < 0.05). Conclusion: Social skills deficits were quite high in depressed Thai patients. The severity of depression and introvert personality were significantly associated with the patients’ social skills. The social skills enhancing program may help reduce patients’ depressive symptoms.